Entre "sâns expansões do espírito" e "sarrilhos dos diabos": lazer, divertimento e vadiagem nas representações da imprensa em Belo Horizonte (1895-1922) - Kellen Nogueira Vilhena (2008)
This paper has as central focus the representation of leisure practices transmited by printing press in Belo Horizonte (1895-1922). Such practices were used in city in different ways: prescribed and authorized; repressed and experimented as a form of resisting and subversion to the present order; praised and supported by the printing press, reproved and denounced by the same press. The documental research was the used methodology focusing the press. Notes, articles, collumns and magazines written in newspapers received special treatment in the first phase of the periodical activities in Belo Horizonte, independently if they have greater or smaller cicrculation. The planning of the new capital of state was also considered having in view the city was able to assume modern and civilized values, according to the republican ideas. Through that analyses was possible to realize that the leisure was also planned, since that change is not restricted to the architectonic aspects, bus also points to the change of the social order. In this scene, the press present itself as a educating institution, with several productions about leisure while transmitting negative and positive representations of one or another practices. The enunciation ways presented in the reports show a high regard to the practices according the new desirable sociability codes, as theater, the cinema, the club parties, the regional band representations, the circus and the footing. Such practices received an incentive and praised references from the press. The same fact did not happen in relation to some practices that were apart from those codes. The inadequate appropriation of the city equipment and permanence of old habits were reproved and considered as caipiras i.e. it is not proper from modern city. The attendance to botequins (cheap taverns) and to gambling sallons was considered as a deviation behavior and was always present in the newspaper in the complaining or police collumns. These practices manifestation show a movement which was marked by the tensions among people who live in the city. It was explicit in the press.